Understanding Hong Kong primary school English teachers' continuance intention to teach with ICT - Bai, Barry; Wang, Jing; Chai, Ching-Sing (Computer assisted language learning, 2021)
There has been an increasing concern on teachers' adoption of information and communication technology (ICT) in their teaching practices. However, little has been explored about English as a second language (ESL) teachers' ICT adoption. This study synthesizes the technology acceptance model (TAM), the value-expectancy theory, and a learning perspective to propose a model -for investigating ESL teachers' continuance intention to use ICT in teaching. In the proposed model, motivational beliefs, ICT learning behaviors, facilitating conditions, and perceptions towards ICT use were put together to see how they worked together to influence continuance intention. Participants were 156 primary school ESL teachers in Hong Kong, who attended a teacher professional development program. Structural equation modeling showed that ICT self-efficacy and facilitating conditions were positively associated with continuance intention through perceptions (i.e. perceived ease of use and perceived usefulness). ICT anxiety had a negative effect, whereas interest had a positive effect on continuance intention. Growth mindset had a positive effect on continuance intention through learning of ICT (i.e. adaptive help seeking). Implications for teachers' professional development programs are discussed.